The Axial Capacity of a Full Height Rectangular Opening Castellated Steel Beam with Steel Reinforcement stiffeners - Muhamad Rusli A.; Prabowo Setiawan (Universitas Islam Sultan Agung, 2021)
The axial capacity of a full height rectangular opening castellated steel beam with steel reinforcement stiffeners is proven to prevent Vierendeel failure mechanism. The effect is an increase in flexural capacity of the structure. Diameter of the steel reinforcement stiffeners is revealed to have an effect on its strength in resisting axial forces occur in the structure. However, size of the diameter is limited to the strength maximum value of the steel flange section in withstanding the moment force. Using optimal design of the castellated steel structure, this research aimed to find out the increase value of the axial capacity. There were two models of steel structures employed in the study, IWF 200x100x5.5x8 and castellated beam 362x100x5.5x8, both were loaded with axial directions. Analyses were conducted using truss and pushover methods. Results of the study showed an increase in both flexural (36.81%) and axial (60.78%) capacities. The increase in the value of structure capacity mainly influenced by the stiffeners shortened the effective length of the structure.